Pertumbuhan dan Produksi Sistem Tumpangsari Rumput Odot (Pennisetum purpureum cv. Mott) dan Ubi Jalar Ungu (Ipomea batatas L. var Antin 3) pada Jarak Tanam yang Berbeda - Nur Aini; Sutarno Sutarno; Sumarsono Sumarsono (JURNAL AGROPLASMA, 2022)
The research was conducted to examine the effect of planting distances of odot grass and purple sweet potato and their interaction to the growth and production. The research was carried out March until August 2021 at Kalongan Village, East Ungaran District, Semarang Regency. The research was used the 2 × 4 factorial experiment with Randomized Block Design of three block replicatin. The first factor is 2 levels of odot grass planting distance T1: 90 × 60 cm and T2: 90 × 45 cm. The second factor is the 4 levels planting distance of purple sweet potatoes V1: 90 × 30 cm, V2: 90 × 40 cm, V3: 90 × 50 cm and V4: 90 × 60 cm. Research parameters the odot grass include plant height, number of saplings, and production of dry matter, in purple sweet potatoes include the length of tendrils, the number of tubers, the production of tuber dry matter, and the production of dry matter. The data processed by the analysis of variance and Duncan Multiple Range Test at 5% level. The results showed that the effect of planting distances of odot grass and purple sweet potatoes had not significant to the growth of odot grass and the growth and production of purple sweet potatoes, but had significant (P<0.05) to dry matter the production odot grass. The planting distance of odot grass at 90 × 45 cm was significant (P<0.05) higher than 90 × 60 cm, and the purple sweet potatoes planting distance of 90 × 60 cm was significant (P<0.05) highest than the treatment of 90 × 40 cm and 90 × 50 cm. Keywords : antin 3, intercropping, odot grass, planting distance,  purple sweet potato.